A FOCUSED REVIEW ON DENTAL PRACTICES FOR PATIENTS WITH SCOLIOSIS - Malik, Ayesha Hina Faisal; Khan , Omar Farooq Ahmad (International Research Journal Diagnostics, 2024)
Scoliosis, derived from the Greek word "Skoliosis," denotes a complex spinal condition characterized by lateral curvature and vertebral rotation. This deformity, often manifesting as a three-dimensional deviation, requires a curvature of over 10° on a PA radiograph for classification as scoliosis. Although commonly diagnosed in children, scoliosis can affect individuals across age groups, with a higher prevalence among girls, often attributed to genetic factors. The etiology-based classification of scoliosis assists in identifying underlying causes, and additional classification systems, such as Kings' and Lenke's, facilitate the diagnosis of curve location, degree, and progression. These systems, in conjunction with clinical assessments, measurements, grading, and imaging studies, contribute to accurate diagnosis and treatment planning.